The Global Prevalence of Amblyopia in Children: A Systematic Review and Meta-Analysis - Hu, Budan; Liu, Zongshun; Zhao, Jiao; Zeng, Li; Hao, Gengsheng; Shui, Dan; Mao, Ke (Frontiers in Pediatrics, 2022)
Epidemiological data about the prevalence of amblyopia around the world vary widely among regions and periods. This meta-analysis aimed to determine the global prevalence of amblyopia in children. PubMed, Embase, and the Cochrane Library were searched for prevalence studies published up to November 5, 2021. The outcome was the prevalence of amblyopia, analyzed as pooled estimates with 95% confidence intervals (CI). A total of 97 studies were included, including 4,645,274 children and 7706 patients with amblyopia. The overall worldwide pooled prevalence of amblyopia was 1.36% (95%CI: 1.27%-1.46%). The prevalence of amblyopia was higher in males (1.40%, 95%CI: 1.10%-1.70%) than in females (1.24%, 95%CI: 0.94%-1.54%) (OR=0.885, 95%CI: 0.795-0.985, P=0.025). The results of the meta-regression analysis showed that there were no significant associations between the prevalence of amblyopia and geographical area, publication year, age, sample size, and whether it was carried out in a developed or developing country (all P>0.05). Begg’s test (P=0.065) and Egger’s test (P<0.001) showed that there was a significant publication bias in the prevalence of amblyopia. In conclusion, amblyopia is a significant vision problem worldwide, and public health strategies of early screening, treatment, and management are important.